Study on the Working Characteristic of Overrunning Alternator Pulley of Automobile Generator - Yi Liu; Guoding Chen (Jixie chuandong)
The Overrunning Alternator Pulley （OAP） of automobile generator is more and more used because it can effectively improve the vibration of the front gear train of the automobile，thus increasing the service life of the gear train. Based on the analysis of the working principle of the OAP of the generator，according to the working mechanism of the OAP of a domestic generator，the virtual prototype model of the bench test of the OAP the automobile generator is constructed by using the multi-body dynamics simulation software RecurDyn. The validity of the calculation method is calculated by comparing with the test data，and the model can be used to realize its working，it is not suitable to calculate the dynamic index for measurement. Through the study of the factors affecting the bearing characteristics and the relationship between them，the direction of design improvement is provided. The research results play an important role in guiding the product design and improving the design level.